The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1172/jci98765
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing NEK2 overcomes resistance to proteasome inhibition in multiple myeloma

Abstract: Drug resistance remains the key problem in cancer treatment. It is now accepted that each myeloma patient harbors multiple subclones and subclone dominance may change over time. The coexistence of multiple subclones with high or low chromosomal instability (CIN) signature causes heterogeneity and drug resistance with consequent disease relapse. In this study, using a tandem affinity purification-mass spectrometry (TAP-MS) technique, we found that NEK2, a CIN gene, was bound to the deubiquitinase USP7. Binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 71 publications
2
70
0
Order By: Relevance
“…These data suggested that NEK2 might elevate Beclin‐1 through blocking proteasomal degradation. We have reported that USP7 binds and stabilizes NEK2 protein (Franqui‐Machin et al , ). NEK2 interacts with both USP7 and Beclin‐1 in MM cells, and we thus hypothesized that NEK2 stabilizes Beclin‐1 via interacting with USP7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggested that NEK2 might elevate Beclin‐1 through blocking proteasomal degradation. We have reported that USP7 binds and stabilizes NEK2 protein (Franqui‐Machin et al , ). NEK2 interacts with both USP7 and Beclin‐1 in MM cells, and we thus hypothesized that NEK2 stabilizes Beclin‐1 via interacting with USP7.…”
Section: Resultsmentioning
confidence: 99%
“…USP7 binds to NEK2 and prevents NEK2 ubiquitination resulting in NEK2 stabilization. Increased NEK2 activates the canonical NF‐κB signaling pathway through the PP1α/AKT axis, which is the downstream targets of USP7‐NEK2 axis (Franqui‐Machin et al , ). In this study, we showed knockdown of Beclin‐1 prevents NEK2‐mediated BTZ resistance in MM both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the DUBs we tested, USP7 has the greatest number of identified substrates, most of which are targeted to the proteasome 61 . Among the substrates that we identified, a few such as MARCH7, SVIL, NEK2A and TRIP12 are known targets of USP7 29, 4446 whereas two others, PIM3 and WASL, are likely USP7 targets as USP7 is known to regulate related proteins (PIM2 47 and WASH 48 respectively) in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach began with identifying proteins protected from proteasomal degradation by cysteine-protease DUBs. Several of these proteins are known to be regulated by specific DUBs, including MARCH7, BIRC3, STAM, NFX1,TRIP12, SVIL, and NEK2A 2932, 4446 . Furthermore, PIM3 and WASL have not been connected previously to DUBs, but are similar in sequence to well-established DUB substrates (PIM2 47 and WASH 48 respectively).…”
Section: Discussionmentioning
confidence: 99%